Knowledge and Attitude of Couples Referring to Kerman Premarriage Counseling Center towards AIDS 2008 - Fatemeh Balali Meybodi; Minoo Mahmoudi Zarandi (Strides in Development of Medical Education, 2010)
Background & Objective : AIDS is not only a health problem but also a sociocultural challenge leading to economic problems Since appropriate health behavior is the result of adequate knowledge and attitude this study was performed on couples referring to Kerman premarriage counseling center to determine their knowledge and attitude towards AIDS and its related factors   Methods : In this crosssectional study 1020 couples participated Data was collected using a questionnaire concerning demographic information and including 22 questions about knowledge and 10 items about attitudes   Results : According to our findings the couples knowledge level was excellent in 401% good in 374% moderate in 20% and poor in 26% The attitude was excellent in 584% good in 335% moderate in 71% and poor in 11% There was a significant relationships between knowledge and attitude with age educational status and career using Chisquare test (P=00001 in all cases) in a way that those with higher educational levels in age group between 16 to 35 years old and employees had better knowledge and a more positive attitude There was also a significant relationship between the attitude and sex (P=00001) male participants showed a more positive attitude compared with women Among sources of knowledge radio and TV were the most frequently mentioned ones (599%)   Conclusion : Our results suggest that TV and radio are the most frequent information resources so improving their related educational programs according to addressed group is necessary More attention to health education in schools accompanied with cooperation and supervision of health sector is recommended